Erythromycin attenuates oxidative stress-induced cellular senescence via the PI3K-mTOR signaling pathway in chronic obstructive pulmonary disease - Xiaofei, Yi; Tingting, Li; Xuan, Wei; Zhiyi, He (Frontiers in Pharmacology, 2022)
Background and Purpose: Chronic obstructive pulmonary disease (COPD) is proposed to hasten lung aging. Erythromycin protects against oxidative stress and inflammatory responses. However, the potential anti-senescence effect of erythromycin remains disclosed. In the present study, we investigated whether erythromycin influenced oxidative stress-induced cellular senescence and investigated its related mechanisms. Methods: A cigarette smoking (CS) -induced emphysema mouse model and a H2O2-induced premature senescence model in human bronchial epithelial cell line (BEAS-2B) were established. Senescence-related markers (P53, P21 and SA-β-Gal activity), and levels of oxidative stress biomarkers (MDA, SOD and ROS) were measured. Additionally, cells were pretreated with rapamycin (mTOR inhibitor) or erythromycin, and the expression levels of components of the PI3K-mTOR signaling pathway were measured in BEAS-2B cells. Results: Exposed to H2O2, increased SA-β-gal activity was observed in BEAS-2B cells suggesting premature senescence. Erythromycin inhibited the expression of P53 and P21 in the CS-induced emphysema mouse model. MDA levels significantly increased and SOD levels decreased in the CS-exposed mice and H2O2-induced BEAS-2B cells. Rapamycin and erythromycin significantly suppressed the expression of P53 and P21. Additionally, rapamycin and erythromycin inhibited the PI3K-mTOR signaling pathway. Conclusion: Our findings suggest that erythromycin ameliorates oxidative stress-induced cellular senescence via the PI3K-mTOR signaling pathway. Hence, we establish a theoretical foundation for the clinical application of erythromycin for COPD prevention and treatment.